The Spectrum of Sensitization in Infants with IgE-Dependent Mechanism of Disease in a Large Industrial Area - O.P. Volosovets; S.V. Vrublevska (Zaslavsky O.Yu., 2015)
Recently, the role of anthropogenic impact on the human bodysignificantly increased, which determines the spread of allergic pathologies in children. Among 318 infants with IgE-dependent skin diseases maximum level of hypersensitivity to food allergens (mostly proteins in chick embryo (34.48 %) and cow's milk (25 %)) and airborne allergens (predominantly to epidermal allergens of domestic animals (28.7 %) and household allergens (29 %)). Creating hyposensitizing effect to the above-mentioned obligate allergens will prevent the development of atopy in young children. Sensitization to fish allergens, wheat, legumes, peanuts, carrots, potatoes wasn't detected in 318 children from experimental group, which makes inappropriate their elimination in accordance with generally accepted guidelines on the prevention of allergic disease in children in Zaporizhzhia region.